Julia Dreisbach: capstone - Dreisbach, Julia, artist (Colorado State University. Libraries, 2025)
The artist's statement: When I began to create art, I was insistent that it was not serving the purpose of therapy. I would have said that I made art because I needed to and it was just who I am. In my practice today I can confidently say that my art has become my therapy. I chose to work with fibers because they are the most relatable material. Every person who looks at my work has had some connection to the material. Whether it be the shirt on their back or a favorite toy from childhood. My work draws on the human ability to self-reflect and analyze hard or painful experiences to create connections with the viewer. In my current body of work, I am drawing on the "big feeling" that I have had in my transition from college into the wider world. I am tackling big emotions like stubbornness, loneliness, and the feeling of being stuck through fibers and animals. I became drawn to the idea of expressing emotions through animals after my roommate got a cat. That cat opened my eyes to the strong bond that people and animals share. Animals like horses and cats have allowed me to project the larger human emotions onto a living canvas to begin to unpack the fear and pride that lie under the unassuming cover. In this body of work, I reach out to my audience by allowing viewers to project themselves into my animals to begin to unpack the "big feelings" they might be feeling too.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers